Characterization of blond and Star Ruby (red) Jaffa grapefruits using antioxidant and electrophoretic methods - Gorinstein, Shela; Drzewiecki, Jerzy; Park, Yong Seo; Jung, Soon Teck; Kang, Seong Gook; Haruenkit, Ratiporn; Toledo, Fernando; Katrich, Elena; Trakhtenberg, Simon (My University, 2006)
Antioxidant and electrophoretic methods were used to characterize the quality differences between blond and Star Ruby (red) grapefruits. Dietary fibre, minerals and trace elements, total polyphenols, anthocyanins, flavonoids, phenolic and ascorbic acids were also determined. The antioxidant potential of red grapefruit was significantly higher than that of the blond fruit (P < 0.05) and correlated well with the total polyphenols (R2 from 0.8456 to 0.9711). In both the cultivars studied, thirty-two electrophoretic bands were detected [sodium dodecyl-polyacrylamide gel eletrophoresis (SDS-PAGE)]. The main electrophoretic bands occurred between 20 and 43 kDa in both grapefruits with few minor differences between the varieties. Our findings indicate the following (i) red grapefruit is preferable: it has a higher concentration of bioactive compounds and antioxidant potential than the blond; (ii) 1, 1-diphenyl-2-picrylhydrazyl (DPPH) test is a more sensitive method for the determination of antioxidant potential; (iii) there are some minor differences in electrophoretic patterns; (iv) antioxidant and electrophoretic methods are a good combination for characterization of differences of the same citrus fruits. © 2005 Institute of Food Science and Technology Trust Fund.
Keywords: β-carotene-linoleate model system; Citrus fruits; Dietary fibre; Gel electrophoresis; Radical scavenging activity; Total polyphenols